Analysis of Freestyle Swimming Techniques in Swimming Course Students - Syahida Cahya Allistia; Ari Gana Yulianto; Eef Robby Nurhidayat (Social, Humanities, and Educational Studies (SHES): Conference Series, 2023)
The aim of this research was to determine the level of basic freestyle swimming technique of students in the Swimming Course of the PJKR Study Program. This research is a descriptive study which aims to describe how to analyze basic freestyle swimming movement techniques for Swimming Course students. Overall research results from 30 students of the Swimming Course of the PJKR STKIP Darussalam Cilacap Study Program who were the samples. The level of freestyle swimming technique mastery obtained was 67%. classified as good, with an error rate of 33%.